Diatom taxonomy and environmental drivers of biodiversity in the Taleghan River and reservoir in Central Alborz, Iran. Issue 3 (3rd July 2022) - Naseri, Ali; Noroozi, Mostafa; Asri, Younes; Iranbakhsh, Alireza; Saadatmand, Sara; Atazadeh, Ehsan
Abstract : The taxonomic composition of the diatom flora of the Taleghan River and reservoir in Iran is described. The Taleghan River is one of the main tributaries of the Sepid Roud River, which is the second-longest river in Iran (∼ 670 km). Its headwaters are located in the Alborz Mountains in northwestern Iran and discharge into the Caspian Sea (North Iran). The current study was conducted from November 2017 to October 2018. A total of 167 taxa belonging to 49 genera and 27 families were identified. Nitzschia (28 spp.) Navicula (20 spp.), Cymbella (12 spp.), and Gomphonema (10 spp.) were the most abundant genera. The identified taxa can be classified as oligosaprobic to eutrophic and Canonical Correspondence Analysis (CCA) showed that temperature, NO3 2−, salinity, turbidity, EC, Si, and DO were the most significant environmental variables influencing diatom assemblages across seasons and sites in the river.